Damage mechanisms in the ultra-low cycle fatigue loading. (January 2020) - Kermajani, M.; Malek Ghaini, F.; Miresmaeili, R.; Baghi-abadi, M.K.; Mousavi-nasab, M.
Highlights: In ULCF condition, damage occurs by fatigue and internal cracks and monotonic voids. Fracture surface analysis determined the contribution of each mechanism. A model was proposed to predict fatigue life of materials exposed to ULCF loadings. Internal cracks form by shear mechanism. Formation of cracks causes gradual decrease of load carrying capacity of materials. Abstract: Predicting extreme limit states in steel structures using finite element simulations requires an understanding of the fracture mechanisms themselves and the relationship of various models to these mechanisms. Aiming at addressing dominant damage mechanisms in the Ultra-Low-Cycle Fatigue (ULCF) regime which occurs during earthquakes, circumferentially notched tensile bars were subjected to cyclic loadings with large displacement amplitudes. Two weld metals from rutile and basic classifications and two different grades of structural steels were selected to determine the role of microstructural features in the response of materials to ULCF conditions. Scanning Electron Microscopy (SEM) technique equipped with 3D measurement software was employed to describe fracture surfaces quantitatively. Moreover, further analyses of hysteresis loops, as well as the structure of the materials beneath the fracture surfaces, provided a better insight into various micromechanisms of damage such as internal cracks involved in ULCF failures. To consider the contribution of all these mechanisms in final failures, fracture surfaces were characterized using "Developed Interfacial Area Ratio" parameter. These results were served to suggest a model for predicting the cyclic life of materials when exposed to ULCF loadings.